2022
DOI: 10.1371/journal.pone.0271242
|View full text |Cite
|
Sign up to set email alerts
|

Survival and complications after neoadjuvant chemoradiotherapy versus neoadjuvant chemotherapy for esophageal squamous cell cancer: A meta-analysis

Abstract: Objectives To compare the survival and complications of neoadjuvant chemoradiation (NCRT) versus neoadjuvant chemotherapy (NCT) for esophageal squamous cell carcinoma (ESCC). Methods We conducted a systematic literature search of the PubMed, Web of Science, Cochrane Library, EMBASE, CNKI, Wanfang Data, CBM, and VIP databases from inception to November 2021. Meta-analyses were performed using RevMan (version 5.3) and Stata version 15.0. Results A total of 18 studies were included, which involved 3137 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Guo et al ‘s meta-analysis found that nCRT could prolong survival, but the reliability of its conclusions was low due to the large number of retrospective studies included in this meta-analysis. [11] Another network meta-analysis by Kelvin et al found that in the direct comparison between nCRT and nCT, there was no significant statistical difference in OS, but indirect comparison showed the opposite result. [10] Our meta-analysis focused only on randomized controlled trials that compared head-to-head nCRT to nCT, and updated recent studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al ‘s meta-analysis found that nCRT could prolong survival, but the reliability of its conclusions was low due to the large number of retrospective studies included in this meta-analysis. [11] Another network meta-analysis by Kelvin et al found that in the direct comparison between nCRT and nCT, there was no significant statistical difference in OS, but indirect comparison showed the opposite result. [10] Our meta-analysis focused only on randomized controlled trials that compared head-to-head nCRT to nCT, and updated recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Due to insufficient data provided by previous randomized trials, some previous meta-analyses included cohort studies, leading to low levels of evidence, unreliable conclusions and some major defects. [11] Moreover, meta-analyses of randomized trials do not support survival benefits of nCRT [12][13][14] ]. So far, the jury is still out on whether to add additional radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, a meta-analysis of 17 randomised controlled trial (RCT)s, including more than 2800 patients, determined that neither neoadjuvant chemotherapy nor chemoradiotherapy were associated with increased risk of anastomotic leakage, a complication of particular concern among surgeons performing oesophageal resection surgery [32]. Other studies have drawn specific attention to increased incidence of pulmonary complications and vocal cord paralysis, although data from a second meta-analysis of 18 studies failed to demonstrate any statistically significant increase in risk for any of the included complications [33].…”
Section: Neoadjuvant Chemotherapy: Is There Significant Risk?mentioning
confidence: 99%